Artist‐Related Determinants of Music Concert Prices. Issue 8 (August 2014) - Decrop, Alain; Derbaix, Maud; Colbert, François
ABSTRACT Ticket prices of pop/rock concerts have risen considerably over the last decade. Reasons for this growth are debatable: the monopolistic position of one concert promoter, the development of mass culture and fanaticism, or changes in artists' business model due to illegal downloading. This empirical paper identifies artist‐related variables that play a significant role in the pricing of music concerts. Referring to economic principles (e.g., transaction costs, economies of scale) and psychological theories (e.g., preferences, signaling), six hypotheses were tested using a unique database covering a period of seven years and containing information on 2687 concerts organized in Belgium as well as on performing artists. Results show that artists' career, nationality, and their popularity are the major determinants of ticket prices.